Poland-Iran relations during the presidency of Hassan Rouhani: An analysis of selected external determinants - Przemysław Osiewicz (Siyasal: Journal of Political Sciences)
The main purpose of this article is to analyze the impact of external determinants on Poland-Iran political relations during the presidency of Hassan Rouhani between 2013-2021. The analysis is based on a set of external conditions that determine their bilateral relations. These include the nuclear agreement concluded with Iran in 2015, the policy of the United States with particular emphasis on the extended sanctions imposed on Iran, the European Union’s policy toward Iran, as well as Iran’s rivalry with some states of the Middle East region. The author has applied qualitative content analysis as the main research technique. The main hypothesis is as follows: external factors determine Polish foreign policy toward the Islamic Republic of Iran due to Poland’s membership in the UN, EU and NATO, as well as economic ties with the Arab states in the Persian Gulf and close relations with the USA.